Lecithin:Cholesterol Acyltransferase Deficiency Protects against Cholesterol-induced Hepatic Endoplasmic Reticulum Stress in Mice - Hager, Lauren (American Society for Biochemistry and Molecular Biology, 2012)
We recently reported that lecithin:cholesterol acyltransferase (LCAT) knock-out mice, particularly in the LDL receptor knock-out background, are hypersensitive to insulin and resistant to high fat diet-induced insulin resistance (IR) and obesity. We demonstrated that chow-fed Ldlr−/−xLcat+/+ mice have elevated hepatic endoplasmic reticulum (ER) stress, which promotes IR, compared with wild-type controls, and this effect is normalized in Ldlr−/−xLcat−/− mice. In the present study, we tested the hypothesis that hepatic ER cholesterol metabolism differentially regulates ER stress using these models. We observed that the Ldlr−/−xLcat+/+ mice accumulate excess hepatic total and ER cholesterol primarily attributed to increased reuptake of biliary cholesterol as we observed reduced biliary cholesterol in conjunction with decreased hepatic Abcg5/g8 mRNA, increased Npc1l1 mRNA, and decreased Hmgr mRNA and nuclear SREBP2 protein. Intestinal NPC1L1 protein was induced. Expression of these genes was reversed in the Ldlr−/−xLcat−/− mice, accounting for the normalization of total and ER cholesterol and ER stress. Upon feeding a 2% high cholesterol diet (HCD), Ldlr−/−xLcat−/− mice accumulated a similar amount of total hepatic cholesterol compared with the Ldlr−/−xLcat+/+ mice, but the hepatic ER cholesterol levels remained low in conjunction with being protected from HCD-induced ER stress and IR. Hepatic ER stress correlates strongly with hepatic ER free cholesterol but poorly with hepatic tissue free cholesterol. The unexpectedly low ER cholesterol seen in HCD-fed Ldlr−/−xLcat−/− mice was attributable to a coordinated marked up-regulation of ACAT2 and suppressed SREBP2 processing. Thus, factors influencing the accumulation of ER cholesterol may be important for the development of hepatic insulin resistance.